2018
DOI: 10.1111/1759-7714.12887
|View full text |Cite
|
Sign up to set email alerts
|

LRH1 as a promising prognostic biomarker and predictor of metastasis in patients with non‐small cell lung cancer

Abstract: BackgroundLRH1, which promotes the malignant transformation of carcinoma, has recently been documented in several types of malignancies. However, LRH1 has not been assessed as a potential clinical biomarker in any cancer.MethodsLRH1 expression was tested in fresh‐frozen tissue samples with quantitative real‐time PCR and Western blot analysis. Surgically resected tumor tissues were collected from 156 non‐small cell lung cancer (NSCLC) patients: 75 with adenocarcinoma and 81 with squamous cell carcinoma. Subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 39 publications
4
21
0
Order By: Relevance
“…The protein and mRNA levels of LRH1 are upregulated in various cancers [15][16][17], We found the same conclusion in our results. Lin et al viewed LRH1 as a remrkable prognosis biomarker for tumor invasion and proliferation in pancreas cancer [34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The protein and mRNA levels of LRH1 are upregulated in various cancers [15][16][17], We found the same conclusion in our results. Lin et al viewed LRH1 as a remrkable prognosis biomarker for tumor invasion and proliferation in pancreas cancer [34].…”
Section: Discussionsupporting
confidence: 90%
“…Liver receptor homolog 1 (LRH1), also known as nuclear receptor subfamily 5 group A member 2 NR5A2, participates in various biological processes, such as liver and pancreas differentiation, steroidogenesis in childhood, cholesterol/bile acid homeostasis, and tumor progression [10,11]. Previous studies validated that the overexpression of LRH1 may induce the resistance of breast cancer to chemotherapy [12,13], the metastasis of pancreas cancer [14], the poor prognosis of colon cancer [15] and non-small cell lung cancer [16], and the proliferation of hepatoblastoma [17]. However, LRH1 expression has not yet been reported in patients with OC.…”
Section: Introductionmentioning
confidence: 99%
“…21 Previous studies have reported the effect of NR5A2 on a variety cancers. Liu et al, 22 confirmed that NR5A2 was related to non-small-cell lung cancer metastasis, progression, and poor prognosis. Meinsohn et al, 23 found that NR5A2 promoted cell proliferation and played as a regulator in ovarian cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Overexpression as well as increased LRH-1 activity had been implicated in a wide variety of human malignancies. [54][55][56][57][58][103][104][105] Affecting multiple distinct signaling pathways, uncontrolled LRH-1 activity stimulates cell proliferation and increases cell viability, and thereby contributes to growth, progression, and aggressiveness of tumors. Several mechanisms possibly contribute to aberrant LRH-1 activity in malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…89 Even though less well studied up to now, LRH-1 deregulation is also associated with tumorigenesis of HCC, [100][101][102] gastric cancer, 92,93 Barrett's-associated adenocarcinoma, 103 prostate cancer, 104 and NSCLC. 63,105,106 However, the mechanisms that underlie LRH-1-regulated proliferation seem to be common among all cancer types analyzed: induction of c-Myc, cyclin D1/E1, and WNT/beta-catenin signaling. Simultaneously, by repressing p21 transcription, LRH-1 promotes carcinogenesis and development of cancerous cells.…”
Section: Lrh-1 As An Oncogene and Associated Functions In Cancermentioning
confidence: 99%